2023
DOI: 10.3390/hydrology10090182
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Groundwater Contamination Vulnerability Assessment Techniques: A Systematic Review

Arghadyuti Banerjee,
Leo Creedon,
Noelle Jones
et al.

Abstract: Assuring the quantity and quality of groundwater resources is essential for the well-being of human and ecological health, society, and the economy. For the last few decades, groundwater vulnerability modeling techniques have become essential for groundwater protection and management. Groundwater contamination is highly dynamic due to its dependency on recharge, which is a function of time-dependent parameters such as precipitation and evapotranspiration. Therefore, it is necessary to consider the time-series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…However, they fail to consider the dynamic changes affecting hydrogeological parameters that compile vulnerability assessment methods, such as climate variations and overexploitation of groundwater reserves, which in uence both recharge and the depth of the groundwater table. Various research studies have demonstrated the temporal and spatial variability of intrinsic vulnerability in aquifers (Banerjee et al, 2023;Es Saouini et al, 2014;Krogulec et al, 2019). The term "intrinsic" is speci cally attributed to the fundamental and permanent characteristics that de ne the nature and functioning of an object (aquifer).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they fail to consider the dynamic changes affecting hydrogeological parameters that compile vulnerability assessment methods, such as climate variations and overexploitation of groundwater reserves, which in uence both recharge and the depth of the groundwater table. Various research studies have demonstrated the temporal and spatial variability of intrinsic vulnerability in aquifers (Banerjee et al, 2023;Es Saouini et al, 2014;Krogulec et al, 2019). The term "intrinsic" is speci cally attributed to the fundamental and permanent characteristics that de ne the nature and functioning of an object (aquifer).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the components of parametric methods, such as the DRASTIC and SINTACS models, and found that the aquifer recharge and depth are dynamic parameters. At the same time, the other parameters are considered static and are not affected by changes or surface pressure (Banerjee et al, 2023;Bouchnan et al, 2014;Cervantes-Servin et al, 2023b;Krogulec et al, 2019).…”
Section: Introductionmentioning
confidence: 99%